Local Wisdom in Designing Interior Design, Review of Cultural Arts and Design Style - Suroso Putro, Tunjung Atmadi; Putra, Yananto Mihadi; Ramadhan, Ali (Universitas Mercu Buana, 2019)
Local wisdom is a system of values and norms that are arranged, practiced, understood and applied to local communities based on the understanding and their experience in interacting with the environment, in the development of interior design, local wisdom It can also be very instrumental in the design of interior design. Can collaborate on styles of interior design can be realized, it will be very interesting interior design, as well as safe, comfortable and harmonious. Based on the above, then the exposure in this study the author wanted to examine the application of the local wisdom in designing interior design that is associated with the development of the design.Â The methods used in this study is a qualitative descriptive method, approach to interior design pragmatically, topologies and have that is an important element in the design. The concept of Paul Laseau how to review the achievement of the concept of local wisdom applied in the process of designing the interior design. Special purpose to be achieved in this research is publication research and development results through on higher education, Journal of national and international journals. Expected in this research study is to apply the concept of local wisdom on designing the interior design, which is applied to the shaper of space.